FUNGI MIKORIZA ARBUSKULA PADA RIZOSFER Pericopsis mooniana (Thw.) Thw. DI SULAWESI TENGGARA - Husna Husna; Sri Wilarso Budi R; Irdika Mansur; Cecep Kusmana; Kartini Kramadibrata (BERITA BIOLOGI, 2014)
The research was conducted with the aim to identify species of arbuscular mycorrhizal fungi (AMF) associated with nedum [Pericopsismooniana (Thw.) Thw.]. Soil sampling was conducted in 6 locations of nedum habitat in South-east Sulawesi. The results showed that nedum associated with 15 species of AMF that belonging to 5 families and 9 genera, Acaulosporaceae (Acaulospora scrobiculata and A. delicata), Claroideoglomeraceae (Claroideoglomus etunicatum), Glomeraceae (Glomus aggregatum, G. boreale, G. canadense, G. halonatum,G. versiforme, Rhizophagus diaphanus, R. fasciculatus, Sclerocystis clavispora and Septoglomus constrictum), Gigasporaceae (Racocetragregaria and Scutellospora auriglobosa), Ambisporaceae (Ambispora appendicula). The four species of AMF were found on nedum, i.e Glomus boreale, G. canadense, G. halonatum and Racocetra gregaria which were a new record for mycological collection of Indonesia.